Pengembangan Panduan Konseling Cognitive Behavioral dengan Teknik Mindfulness untuk Mengatasi Trauma pada Anak-anak Korban Kekerasan Seksual - Luh Putu Yuli Surya Dewi; Kadek Suranata; I Ketut Gading (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2022)
This study aims to (1) describe the design of the counseling guide, (2) find and analyze the magnitude of the effectiveness of implementation counseling guide, (3) find out the practicality of the guidebook, and (4) find out the acceptability of the cognitive behavioral counseling guide with mindfulness techniques to address child victims of sexual violence. This research use Research and Development (R&D) method with 4D models (Four D), and use a traumatic scale questionnaire instrument. Expert testing of the guidebook product involved 4 experts from Guidance and Counseling, as well as 1 expert from the Sanglah General Hospital Psychologist and 1 expert from Buleleng District General Hospital Psychiatrist. The results of this study indicates (1) produce a cognitive behavioral counseling guidebook, (2) the validity of the manual using the Lawshe formula, the results are obtained CVR each item is 1 (CVR>0). CVI score obtained is 1, it can be stated that the feasibility of this guidebook is high for further development, (3) the practicality test of the guidebook on the assessment of 5 practitioners in P2TP2A was stated to be very practical (92%), (4) the effectiveness of the guidebook obtained a significant value of 0.000 or less than 0.05, it means the cognitive behavioral counseling manual is effectively used to overcome trauma to child victims of sexual violence in Buleleng Regency.